2010
DOI: 10.1246/cl.2010.1188
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-15 NMR Spectroscopy of Sugar Sensor with B–N Interaction as a Key Regulator of Colorimetric Signals

Abstract: Nitrogen-15 NMR spectroscopy showed strongly upfield values of the chemical shift for one of the azo nitrogen atoms of a boronic acid appended azo dye; this indicated the formation of a boron-nitrogen (B-N) dative bond. The B-N dative bond was cleaved by sugar addition.Boronic acids are widely used for sugar sensors because they react with diol moieties of sugars to form boronate esters. 1 Sugar sensors based on boronic acids require the occurrence of signal changes upon sugar binding. James et al. have develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…We introduced a boronic acid group to the o -position of the azo group. Some o -boronic acid substituted azobenzenes were successfully synthesized with diazo-coupling reactions [ 65 , 66 ]. An azo dye, 6 ( Figure 5 ), which has a basic skeleton of a series of o -boronic acid substituted azobenzenes, shows an absorption maximum at 505 nm in aqueous MeOH, which is significantly red-shifted compared to that of 4-aminoazobenzene (365 nm) [ 67 ].…”
Section: O -Boronic Acid Substituted Azobenzenementioning
confidence: 99%
See 3 more Smart Citations
“…We introduced a boronic acid group to the o -position of the azo group. Some o -boronic acid substituted azobenzenes were successfully synthesized with diazo-coupling reactions [ 65 , 66 ]. An azo dye, 6 ( Figure 5 ), which has a basic skeleton of a series of o -boronic acid substituted azobenzenes, shows an absorption maximum at 505 nm in aqueous MeOH, which is significantly red-shifted compared to that of 4-aminoazobenzene (365 nm) [ 67 ].…”
Section: O -Boronic Acid Substituted Azobenzenementioning
confidence: 99%
“…In order to gain insight into the B–N interaction, we used 15 N NMR spectroscopy, because the formations of coordination bonds are sensitively reflected in the 15 N chemical shifts [ 70 , 71 ]. We synthesized a 15 N-labelled azo dye ( 8 , Figure 8 ), which corresponds to dye 6 [ 66 ].…”
Section: Investigation Of B – N Interactions Usingmentioning
confidence: 99%
See 2 more Smart Citations
“…These sensors exhibit a marked color change caused by the rehybridization of the boron center from sp 2 (boronic acid) to sp 3 (boronate ester) when reacted with sugars. In particular, Egawa et al reported o -azophenylboronic acids ( azoB s) with excellent features for the colorimetric detection of sugars, one of which shows a color change from red (λ max = 521 nm) to yellow (λ max = 398 nm) in response to d -fructose. , Some azoB -based applications have already been established, such as dye-modified polymers, , imprinted hydrogels, and functionalization of Au superparticles . In these reports, the drastic color change upon reaction with d -fructose was attributed to the direct N–B dative bond between the β-N atom of the azo group (Chart ) and the boron center of boronic acid.…”
Section: Introductionmentioning
confidence: 99%